Exploration of the multidirectional stability and response of prefabricated volumetric modular steel structures - Chen, Zhihua; Khan, Kashan; Khan, Arsalan; Javed, Khadija; Liu, Jiadi (Journal of constructional steel research, 2021)
Prefabricated volumetric modular steel construction (PFVMSC) has a sustainable behaviour that reduces construction time, waste resources, and onsite workload, resulting in improved quality, faster, safer, and more environmentally sustainable construction. This gradually encourages its adaptation to modern urbanisation as an acceptable alternative to traditional construction in multi-storey structures. The structural instability is not noticeable in low-rise buildings and low seismic zones, so PFVMSC is frequently used. However, lateral loads from winds and earthquakes in high seismic zones significantly impact high rise modular steel building (MSB) since the building's height rises. Thus, PFVMSC's applicability to high-rise engineering projects is hampered by a lack of information about high-rise structures' stability due to extreme multidirectional forces. Therefore, this research summarises key technical issues related to the structural stability and robust performance of multi-storey PFVMS structures. Because of the study's versatility, the module classification is briefly introduced to PFVMSC, followed by a structural system discussion. The structural response of the stability systems and recent connection advancements, on which the multidirectional structural stability of multi-storey PFVMS buildings is highly dependent, is discussed in detail. It was accompanied by a summary of the associated challenges, structural requirements, a research evaluation of recent advancements and associated performance studies that can significantly improve multi-level vertical stacking and multidirectional force transmission. Despite increased research into PFVMSC's structural performance, a thorough understanding of the subject has yet to be gained, posing a threat to its continued prevalence in multi-storey buildings and areas where hazardous events may occur. As a result of this development, numerous significant research sectors have proposed expanding the use of PFVMSC on a multi-storey level. [Display omitted] •The introduction part examined the various types and configurations of modular units used worldwide in terms of materials and load resistance in order to determine why steel is so widely utilised in manufacturing.•Numerous solutions for multidirectional stabilisation have been identified based on advanced research, patents, and engineering applications worldwide.•On the basis of critical study findings, the multidimensional structural responses of MSB are explored.•Globally adopted design methodologies, including design standards and computational design tools, were examined.•Additional research objectives were proposed to address identified issues and potential solutions.